Odpowiedzi

2010-03-09T16:43:12+01:00
A. 3x+4x+5y-2y=7x+3y
7x+3y=7x+3y
7x-7x=3y-3y
0=0

b.2a-3a+7-6
-a+1

c. 2x-5x+7-x
-4x+7

d.2a+b-4b
2a-3b

e.x-2x+3+x-4
-1

f.3x-y+4x-2y
7x-3y

g.2x-6+4x+2
6x-4

h.3y-5-5y-6
-2y-11

i.-2a+2b-3a-3b
-5a-b

j.¹₂t-2x+3t-x-t
2,5t-3x
1 1 1
2010-03-09T16:43:15+01:00
B.2a-3a+7-6=-a+1
c. 2x-5x+7-x=-4x+7
d.2a+b-4b=2a-3b
e.x-2x+3+x-4=-1
f.3x-y+4x-2y=7x-3y
g.2x-6+4x+2=6x-4
h.3y-5-5y-6=-2y-11
i.-2a+2b-3a-3b=-5a-b
j.¹₂t-2x+3t-x-t=2½t-3x
1 2 1
  • ZuZX
  • Rozwiązujący
2010-03-09T16:45:00+01:00
A. 3x+4x+5y-2y=7x+3y
7x+3y=7x+3y
7x-7x=3y-3y

b.2a-3a+7-6
a+1

c. 2x-5x+7-x
-34x+7

d.2a+b-4b
2a-3b

e.x-2x+3+x-4
-1

f.3x-y+4x-2y
7x-3y

g.2x-6+4x+2
6x-4

h.3y-5-5y-6
-2y-11

i.-2a+2b-3a-3b
-5a-b

j.¹₂t-2x+3t-x-t
2½t-3x
1 1 1